Effect of leptin level in non insulin dependant (type 2) obese diabetic subjects - Majeed, Maysaa J.; Othman, Othman G. (Journal of the Faculty of Medicine Baghdad, 2009)
Background: Determine how do obesity and type2 diabetes intertwined? and what it takes to turn an obese person into a person with diabetes. That link may help to understand why some obese people never develop diabetes while many others do. Serum sugar level was used as indicator of insulin level; leptin level was used as indicator of leptin resistance. A total of 50 obese subjects were involved in this study, 25 obese subject (BMI >30) had diabetes mellitus type 2(no insulin dependant), selected from Baghdad teaching Hospital in Baghdad /Iraq. The remaining 25 obese (BMI >30) were normal healthy individuals. Patients and Methods: ELSA technique was used for the measurement of serum leptin. Blood sugar was determined by using colorimetric method. Data were expressed as mean ± SD results and were evaluated using the student t-test for paired data. Conventional methods were used for the correlation and regression analyses. Results: Obtained results showed that the level of serum leptin in healthy obese subjects were significantly lower than that of obese diabetes subjects. , serum sugar in non diabetic obese subjects was significantly lower than obese diabetes type2 subjects. Serum leptin correlated negatively with level of serum sugar at the same time had a positive correlation with BMI in non diabetic obese group whereas level of serum leptin correlated positively with each of BMI and serum sugar in diabetic type2 group. All results are thoroughly discussed in the text. Conclusion: The present study indicates the possibility of future development of a new class of anti diabetic agents that act centrally and independent of insulin action.